TOKSISITY EXSTRACT SEAWEEDS E. cottoniiwith N-HEKSANA SOLVENT AND ETIL ASETAT TO BRINE SHRIMP Artemia salina - Hardiko, Syefri; Nurrachmi, Irvina; Mulyadi, Aras (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTSeaweeds have cultivation potential which is one of the most main export product Indonesian country. Several research about species Eucheuma cottonii previously found some new advantages the one is natural antiseptic. This research was conducted in March to April 2018 at Laboratory of Natural and Mineral Materials Department of Chemical Engineering, Faculty of Engineering, University of Riau and Laboratory of Marine Chemistry. The purpose of this research is to obtain seaweed extract E. cottoni with n-heksana and etil asetat solvent and to know toxicity value seaweed extract. The method used to analyze this research is experiment. This research used rancangan acak lengkap (RAL). The handling was conducted with giving different concentration handling from Artemia salina (10, 100, 1000 ppm) by three repetitions. The results showed that extract levels which is obtained using etil asetat solvent is 350 mL, while n-heksana extract is obtained inadequate to tested. Extract value LC50etil asetat E. cottoni 22,1870 ppm. Keyword : Toksisitas, Eucheuma cottonii, N-heksana, Etil Asetat